1986
DOI: 10.1002/esp.3290110108
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐sieving: A method for grain‐size analysis of coarse‐grained, unconsolidated bedding surfaces

Abstract: The photo-sieving method enables the grain-size analysis of particles > 10 mm from unconsolidated openwork bedding surfaces. The accuracy is equal to the machine-sieving method. The sediment surface is photographed in the field using a camera stand. The enlarged print is digitized for computer processing by tracing the outlines of the pebbles. From the size and shape of the projection area of the individual pebble images the computer determines the ellipsoids of revolution, classifies these ellipsoids, and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 11 publications
2
92
1
1
Order By: Relevance
“…Given that the validation data consisted of bulk samples and that the calibration data consisted in photosieving grain size data, a bias was expected during validation. The obtained bias of À1.4% therefore seems to support the findings of Ibbeken and Schleyer [1986], who found that the bias associated to photosieving was sufficiently small to neglect correction factors. Furthermore, the small reported bias confirms field observations that clasts in the study river are generally weakly imbricated.…”
Section: Grain Size Data Qualitysupporting
confidence: 88%
See 3 more Smart Citations
“…Given that the validation data consisted of bulk samples and that the calibration data consisted in photosieving grain size data, a bias was expected during validation. The obtained bias of À1.4% therefore seems to support the findings of Ibbeken and Schleyer [1986], who found that the bias associated to photosieving was sufficiently small to neglect correction factors. Furthermore, the small reported bias confirms field observations that clasts in the study river are generally weakly imbricated.…”
Section: Grain Size Data Qualitysupporting
confidence: 88%
“…These methods typically rely on photographs of the bed. Also called photosieving, they involve taking plan view images of gravels either in exposed areas [Adams, 1979;Ibbeken and Schleyer, 1986;Butler et al, 2001a] or shallow submerged areas [Whitman et al, 2003]. Generally, images of the riverbed are collected from standing position with some form of scale information in each image.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Either the linear technique developed by Wolman (1954) or the photo-sieving technique developed by Ibbeken and Schleyer (1986) was used on the emerged bars, depending on the characteristics of the section. The latter technique entails photographing a zone of 1 m 2 through a grid of square sections (10 cm by 10 cm).…”
Section: Sediment Sizementioning
confidence: 99%